2021
DOI: 10.1038/s41598-021-93627-5
|View full text |Cite
|
Sign up to set email alerts
|

Renal markers and risks of all cause and cardiovascular mortality from the Taichung community based cohort study

Abstract: This study aimed to explore the associations between renal-related and arterial stiffness biomarkers with all-cause and expanded cardiovascular disease (CVD) mortality in a general Taiwanese population. This prospective community-based cohort study included 4883 subjects aged ≥ 20 years who were followed up until December 31, 2016. Renal-related biomarkers consisted of blood urea nitrogen (BUN), estimated glomerular filtration rate (eGFR), and urine albumin-to-creatinine ratio (UACR). Arterial stiffness biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Besides, both the risk of all-cause and CV death caused by elevated UACR increased with the worsening of glucose regulation, with HR of all-cause death increasing from 1.81 to 2.15 and HR of CV death increasing from 2.39 to 3.39 in pre-DM and DM people respectively. Our results supported the previous studies, [15][16][17][18]30 which indicated the close relationship between elevated UACR and all-cause and CV mortality. However, most studies conformed the value of elevated UACR to predict all-cause and CV mortality in diabetic and general population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Besides, both the risk of all-cause and CV death caused by elevated UACR increased with the worsening of glucose regulation, with HR of all-cause death increasing from 1.81 to 2.15 and HR of CV death increasing from 2.39 to 3.39 in pre-DM and DM people respectively. Our results supported the previous studies, [15][16][17][18]30 which indicated the close relationship between elevated UACR and all-cause and CV mortality. However, most studies conformed the value of elevated UACR to predict all-cause and CV mortality in diabetic and general population.…”
Section: Discussionsupporting
confidence: 93%
“…The research of Hoorn Diabetes Care System cohort showed increased UACR (>3.0 mg/mmol) was prospectively associated with a higher risk of CV mortality in type 2 DM patients 16 . The same phenomenon was also found in general population 17 . However, a study by Siddique et al reported mildly increased albuminuria (UACR ≥10 and <30 mg/g) was a significant predictor of all‐cause and CV death in those with type 2 DM 18 .…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our nomogram showed that the levels of hemoglobin and albumin had negative association with the risk score of mortality. BUN is a sensitive index for reflecting renal function, many studies suggested BUN was associated with increased all-cause mortality in various populations [ 55 , 56 ]. BUN could reflect the whole health status and functional level in the general older population [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood urea nitrogen (BUN), a product of the metabolism of nitrogen compounds, was described to be associated with mortality in various human diseases. Elevated BUN regarding renal dysfunction is associated with the increased risk of incident diabetes (7) and mortality in cardiovascular diseases (8)(9)(10). A non-linear correlation between BUN and post-operative 30-day mortality was reported in patients with sepsis (11).…”
Section: Introductionmentioning
confidence: 99%